Avaliação da frequência de HLA-B*51 e seus principais alelos em paciente brasileiros com Doença de Behçet. - Agustinelli, Joice Moraes Faria Monteiro Belem [UNIFESP] (2019)
Behcet's disease (BD) is a systemic inflammatory disease characterized by recurrent oral and genital ulcers, skin lesions and ocular, articular, intestinal, neurological and/or vascular involvement. HLA-B*51 a split product of HLA-B*5 is considered the main genetic marker associated with BD, mainly in the Silk Road countries, where its prevalence ranges from 40-80%, while this prevalence is only 13% in Caucasian individuals with BD. The prevalence of HLA-B*51 and its subtypes is not known in Brazilian patients with BD, and associations between HLA-B*51 or its subtypes as a risk factor for developing BD in our population is not known as well. Objective. To evaluate the prevalence of HLA-B*51 in Brazilian BD patients and to compare it to healthy controls (HC); to assess whether there is an association between the presence of the subtypes HLA-B*51:01/HLA-B51*08 and a higher risk for DB in the Brazilian population; to assess whether there is a negative association between the presence of HLA-B*51:07 and DB in Brazilian individuals and to evaluate the association between HLA-B*51 and its subtypes with specific manifestations of BD. Patients and Methods: a cross-sectional study was performed with BD patients and HC. HLA-B*51 was detected by polymerase chain reaction with sequence-specific primer (PCR-SSP). Subsequently, positive samples for HLA-B*51 underwent genetic sequencing by the Sanger method to detect HLA-B*51 subtypes. Results. Eighty-three BD patients and 258 HC were evaluated. HLA-B*51 was found in 30.1% of BD patients and in 15.5% of HC (p = 0.003). The most prevalent subtypes in DB patients were HLA-B*51:01 (18.1%), HLA-B*51:08 (6.0%), HLA-B*51:22 (2.4%), HLA-B*51:29 (2.4%) and HLA-B*51:02 (1.2%), while HLA-B*51:01 (12.0%) and HLA-B*51:55 (1.2%) were more prevalent in HC. HLA-B*51 was less frequently found in patients with neurologic involvement (8.0% vs. 29.3%; p = 0.034) while HLA-B*51:01 was more observed in patients with ocular involvement (93.3% vs. 60.3%; p = 0.014). No BD patient with neurologic or vascular involvement presented HLA-B*51:01. HLA-B*51:08 was more frequent in patients with vascular manifestations (60.0% vs. 15.4%; p = 0.012). In multivariate analysis, HLA-B*51 was an independent risk factor for BD (OR = 2.410; 95CI: 1.332-4.361; p = 0.004) and HLA-B*51:08 had an independent association with vascular manifestations of BD (OR = 14.843; 95CI: 1.550 - 142.115; p = 0.019). Conclusions. The prevalence of HLA-B*51 is higher in Brazilian BD patients compared with HC, and it is a risk factor to the development of the disease. HLA-B*51:01 is the subtype most frequent in both BD patients and HC, and it is not a risk factor for BD or for disease manifestations. HLA-B*51:08 is independently associated with vascular manifestations in BD. No HLA-B*51:07 was found in BD patients or in HC in this study.